Distinguishing Stoichiometric Homeostasis of Soil Microbial Biomass in Alpine Grassland Ecosystems: Evidence From 5,000 km Belt Transect Across Qinghai–Tibet Plateau - Fan, Jihui; Liu, Tianyuan; Liao, Ying; Li, Yiying; Yan, Yan; Lu, Xuyang (Frontiers in Plant Science, 2021)
The biogeographic characteristics of microbial stoichiometry homeostasis as well as its mechanisms are commonly thought to be key factors for survival strategies and resource utilization of soil microbes under extreme habitat. In this study, we conducted a 5000 km transect filed survey in alpine grassland across Tibetan Plateau in 2015 to measure soil microbial biomass carbon (MBC) and nitrogen (MBN) across alpine steppes and meadows. Based on the differences of climate and soil conditions between alpine steppe and meadow, the homeostasis coefficients and correlation coefficients were calculated to investigate the homeostatic degree of MBC, MBN and the ratio of MBC to MBN. Furthermore, the “trade-off” model was utilized to deeply distinguish the homeostasis degree of MBC/MBN between alpine steppes and meadows, and the regression analysis was used to explore the variability of trade-off in response to environmental factors in alpine grasslands. Our results show that the coefficient of variation (CV) of MBC/MBN in alpine meadows (CV=0.4) was lower than alpine steppes (CV=0.7), and the homeostasis coefficient (H) of MBC/MBN across alpine meadows (H=10.29) was higher than steppes (H=3.71). According to the trade-off model, microbial turnover activity of soil nitrogen relative to soil carbon increased rapidly and then decreased slightly with soil organic carbon (SOC), soil total nitrogen (STN) and soil water content across alpine meadow. Nevertheless, in alpine steppes, SOC/STN had positive effect on microbial turnover of soil total nitrogen. These results suggest that across TP’s alpine grasslands, water, heat and soil nutrient availability are critical factors influencing stoichiometric homeostasis of soil microbial biomass C:N which in alpine meadows was more stable than that in alpine steppes for the reason that microbial living strategy of the trade-off demands between soil carbon and nitrogen is different in alpine steppes and meadows, resulting in different patterns and mechanism of microbial stoichiometry homeostasis.